Total skin electron beam therapy - Specht, Lena (Frontiers in Oncology, 2025)
Primary cutaneous lymphomas are highly radiosensitive. X-rays work well for localized cutaneous lymphomas. However, if disseminated in the skin and covering larger areas, as is commonly the case with the most common type, mycosis fungoides, x-ray therapy is not suited because the dose to underlying organs exceeds their tolerance. By contrast, electrons have a limited range of penetration, and are ideal for treating superficial lesions. Techniques have been developed to yield a fairly uniform dose to the entire skin surface and treating to a depth of about 1-1½ cm. Total skin electron beam therapy (TSEBT) is probably the most effective skin directed therapy for widespread primary cutaneous lymphomas. For many years the total dose used for mycosis fungoides was 30-36 Gy, given in small fractions. This treatment could only be repeated once. However, total doses of 10-12 Gy have now been shown to offer excellent response rates, and the treatment can be repeated up to 6 times, offering as much or probably even more palliation than the high-dose treatment. Today, most patients are treated with low-dose TSEBT, the higher doses reserved for patients with more resistant disease. Attempts have been made to use photon therapy for total skin irradiation, e.g., tomotherapy. However, even with the most meticulous of techniques there is too much dose in deeper structures, resulting in bone marrow toxicity even with low-dose treatment. This is never seen with electrons, even with high-dose therapy. Further research into optimizing TSEBT and exploring combinations with systemic treatments is ongoing.